The Role of Anthocyanin Content of Garden Balsam’s (Impatiens balsamina L.) Flower Extract on the Growth of Ralstonia solanacearum - Djati Widhityarini; Rani Agustina Wulandari; Triwidodo Arwiyanto (Universitas Gadjah Mada, 2019)
The study was aimed to determine the response of bacterial growth of Ralstonia solanacearum Race I of biovar III phylotype I treated with flower extract of Garden Balsam (Impatiens balsamina L.) on different color of flower, that was able to give the strongest antibacterial compound and to determine the physical characteristics of I. balsamina in order to facilitate the purpose of the garden balsam cultivation as antibacterial. In addition, this study also aimed to determine the highest total anthocyanin content (TAC) and to determine the molecular characteristics of anthocyanin-coding genes and DNA base sequences of I. balsamina that indicated antibacterial properties. The research used Completely Randomized Design (CRD) 2 X 4 each with 3 replications. The first factor was the method of plating bacteria culture (pour plate and streak plate method), the second factor was the color of the garden balsam flower extracts consisted of white, red, purple and magenta. Therefore, the experiment consisted of 8 treatments of combination. Data were analyzed using CRD (α = 0.05). The results showed that the average combination of pour plate and red flower extract gave the value of resistance velocity on the 3rd day with the diameter of the inhibition zone was 33.46 mm, with the inhibitory zone diameter of the garden balsam extract of 22.90 mm. Red flower plants showed a bright red stem on the braches and the pointed leaf edge. Although this red does not show the total content of anthocyanin compounds higher than purple, however from RAPD analysis for red color indicated the anthocyanin of pelargonidin as an anthocyanin compound responsible for its antibacterial properties.